A ideia de dignidade humana em Kant: enquanto lei da liberdade, da justiça e da igualdade - Santos, Marilda Pereira dos (2018)
The aim of the research is to investigate the idea of human dignity in Immanuel Kant. It is based on an analysis of the conceptual ethical elements contained in the Fundamentation of the Metaphysics of Customs, in which Kant presents the formula of humanity, in it the concept of human dignity is constituted in the idea that human beings have an absolute value, as an end in itself. The relevance of research on the idea of human dignity is of fundamental importance in the social context and in the context of the law, however, it is opted to expose its problematic in the moral philosophical context. For this, it is necessary to examine the moral principle according to which man should act, verifying whether it is possible or not to understand this idea of human dignity as a law of freedom, justice and equality. The meticulous examination of these concepts is structured through Kant's argumentative logical exposition, systematizing the concepts of goodwill, duty and imperative, since they make it possible to think about the problem of study which is the formula of humanity. It is therefore a matter of understanding the conceptual framework that serves as a basis for justifying the concept of human dignity, in which it organizes and approaches the concepts of freedom, justice and equality, in order to do the reflexive exercise that establishes the connection between them, whose interest is in the understanding of the question of respect for humanity, with regard to the freedom of man. The methodology used is the bibliographical research of Kantian ethical philosophy. In the first chapter the concepts of man, of good will, of duty and of imperative are exposed through Kant's methodology. Resources used to understand the conceptual framework that underlies Kantian ethics and how these concepts help in understanding the idea of human dignity. In the second chapter we try to deal with the formulas of the imperative, that is, the formula of the universal law, the formula of humanity, the formula of autonomy and the realm of ends. As the subject of research is the question of human dignity, the content is structured around the formula of humanity, trying to show why the human being, in a general way, respects himself and others. In the third chapter, the concept of freedom is firstly exposed, followed by the concept of justice and equality, focusing on the reflexive exercise of promoting the encounter between the concept of human dignity, with the concepts of freedom, justice and equality by checking whether or not this meeting is possible. It is concluded that from the questions used during the research, the concept of human dignity does not change in the confrontation with the concepts of freedom, justice and equality, since Kant presents the moral law, they only reinforce the ideal of humanity.